2010
DOI: 10.1007/s11999-009-1091-4
|View full text |Cite|
|
Sign up to set email alerts
|

THA With Delta Ceramic on Ceramic: Results of a Multicenter Investigational Device Exemption Trial

Abstract: Level I, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
161
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(170 citation statements)
references
References 39 publications
7
161
0
2
Order By: Relevance
“…Although manufacturers reported a stable fracture rate of third-and fourth-generation ceramic liners going from 0.032% to 0.028% [25], this very low rate has not been supported by previous studies, which reported a higher rate of AMC ceramic liners ranging from 1.9% to 2% [7,15] (Table 2). Most of those liner fractures were intraoperative insertional chipping [15] or postoperative fracture resulting from improper initial seating of the modular liner within the metal cup [7,15]. Thus, liner fractures in vivo reported in earlier studies can be explained by technical errors rather than mechanical properties of the AMC ceramics.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Although manufacturers reported a stable fracture rate of third-and fourth-generation ceramic liners going from 0.032% to 0.028% [25], this very low rate has not been supported by previous studies, which reported a higher rate of AMC ceramic liners ranging from 1.9% to 2% [7,15] (Table 2). Most of those liner fractures were intraoperative insertional chipping [15] or postoperative fracture resulting from improper initial seating of the modular liner within the metal cup [7,15]. Thus, liner fractures in vivo reported in earlier studies can be explained by technical errors rather than mechanical properties of the AMC ceramics.…”
Section: Discussionmentioning
confidence: 63%
“…Although these material improvements would be expected to decrease clinical concerns associated with previous-generation alumina bearings such as ceramic fracture and squeaking, little is known about this new bearing material and intermediateterm effects are unclear [7,15,27]. Therefore, we evaluated complications associated with the use of ceramic-on- ceramic AMC bearings and clinical outcomes including HHS and survivorship.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A potential alternative to conventional metalon-PE bearing surfaces is alumina-ceramic-on-ceramic. Historically, these bearing surfaces were associated with catastrophic failures of the ceramic head or liner, such as component fracture and chipping [17,18]. Recently, improvements in manufacturing processes have produced ceramics with smaller grain sizes, lower porosity, and higher density, leading to stronger and more fractureresistant materials [29].…”
Section: Introductionmentioning
confidence: 99%